Allusive Proper Names in the 13th Century Poem “Kissa-I Yusuf” by Kul Gali - KUZMINA, K.KH.; GALIULLINA, G.R.; KAJUMOVA, Z.M.; KAMALIEVA, A.M. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article presents the results of a study of the allusive proper names functioning in the 13th-century literary text “Kissa-i Yusuf” by Kul Gali. The purpose of the research presented in this article is to find and analyze the use of allusive proper names in the poem “Kissa-i Yusuf” (Tale of Yusuf). For studying a combination of descriptive, comparative historical and functional-stylistic methods. The study shows that in the 13th-century poem “Kissa-i Yusuf” by Kul Gali there are proper names that express the author’s intention and represent the way of conveying the author’s conception. RESUMEN El artículo presenta los resultados de un estudio de los nombres propios alusivos que funcionan en el texto literario del siglo XIII "Kissa-i Yusuf" por Kul Gali. El propósito de la investigación presentada en este artículo es encontrar y analizar el uso de nombres propios alusivos en el poema "Kissa-i Yusuf" (Cuento de Yusuf). Para estudiar una combinación de métodos descriptivos, comparativos históricos y funcionales-estilísticos. El estudio muestra que en el poema del siglo XIII "Kissa-i Yusuf" de Kul Gali hay nombres propios que expresan la intención del autor y representan la forma de transmitir la concepción del autor.